Mobile web and intelligent information systems : 16th International Conference, MobiWIS 2019, Istanbul, Turkey, August 26-28, 2019, Proceedings /: 16th International Conference, MobiWIS 2019, Istanbul, Turkey, August 26-28, 2019, Proceedings. (2019) - Unknown
No abstract available